Effect of Maturity Stage and Postharvest Calcium Chloride Treatment on the Quality and Storage Life of Tomatoes (Lycopersicon esculentum Mill) - Arthur, Eric; Oduro , Ibok; Kumah, Patrick (Journal of Postharvest Technology, 2015)
The general purpose of this study was to determine the postharvest quality and  storage life of tomato fruit harvested at 3 maturity stages (breaker, pink and  light red stage) and dipped in different concentrations of CaCl2 (0%, 2% and  6% CaCl2) for 30 minutes. Fruits harvested at the pink stage retained  significantly (P < 0.05) greater weight, higher amount of titratable acidity and  vitamin C than fruits harvested at the light red stage at day 12. All calcium  chloride treated fruits showed a significant (P < 0.05) delay in the changes of  weight loss, firmness, decay, titratable acidity and vitamin C as compared to  the control. Tomatoes harvested at the pink stage and dipped in 6% CaCl2  maintained significantly (P < 0.05) lower weight loss and decay, and as well  retained higher firmness and vitamin C content of the fruits leading to the  extended storage life of the tomato fruit. Therefore, farmers and marketers of  tomato fruits could extend the storage life and reduce weight loss, vitamin C  loss and fruit softening by harvesting at the pink stage and dipping in 6%  CaCl2. This will enhance the flexibility of farmers and traders as to when and  where to market their fresh tomatoes in order to make the maximum profit.
Keywords: Maturity stages; postharvest; quality; storage life